Increasing User Engagement in Re-designed Classic Video Games - Lanitis, Andreas; Michael, Nicholas; El Kater, Alexios (My University, 2013)
The development of low cost 3D visualization devices has prompted an increased interest in interactive Virtual Reality (VR) applications. A key factor in the design and implementation of VR applications is the immersion level that indicates the quality of user experience and level of engagement. In an attempt to enhance the user engagement in VR computer games we explore two distinct directions which include (i) The use of statistical 3D shape modeling and dedicated image processing techniques that enable the generation and subsequent use of personalized avatars in collaborative VR environments and (ii) The adaptation of retro video games to multiuser VR environments. The ultimate aim of our work is to combine the results of the two approaches so users are offered the ability to use their personal avatars in VR classic game environments so that the level of immersion and user satisfaction is maximized.
Keywords: Retro Video Games; Personalized Avatars; Collaborative VR